An analysis of health inequalities depending on educational level using nationally representative survey data in Japan, 2019 - Tasuku Okui (BMC, 2021)
Abstract Background In recent years, socioeconomic differences in health statuses and behaviors have not been investigated from the nationally representative survey data in Japan. In this study, we showed differences in representative health behaviors and statuses depending on educational level using a nationally representative survey data in Japan. Methods Aggregated (not individual level) data from the Comprehensive Survey of Living Conditions in 2019 were used to examine the association between educational level and outcome status of psychological distress (K6 scores > = 5), self-rated health, smoking, alcohol drinking, and cancer screening participation (stomach, lung, colorectal, breast, and uterine cancers). Data of 217,179 households in Japan were aggregated by the Ministry of Health, Labour, and Welfare in the survey, and the data of the estimated number of household members and persons corresponding to each response option for the questions in all of Japan were used. Five-year age groups from 20 to 24 to 80-84 years and over 84 years were analyzed, and the prevalence or participation rate by educational level were calculated. In addition, the age-standardized prevalence or participation rate according to educational level were also calculated by sex. Moreover, a Poisson regression model was applied for evaluating an association of educational level with the outcomes. Results As a result, a clear gradient by educational level was observed in almost all the age groups for the prevalence of psychological distress, poor self-rated health, and smoking and participation rates in cancer screening, and high educational level were associated with better health-related behaviors and statuses. Conversely, drinking prevalence was shown to be higher rather in highly educated people. In addition, a statistically significant association of educational level with all the outcomes was observed. Conclusion It was shown that disparities in health behaviors and statuses still persisted in recent years, and the findings suggested that further measures should be taken to tackle this disparity.